2014
DOI: 10.1002/14651858.cd006811.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Modest cooling therapies (35ºC to 37.5ºC) for traumatic brain injury

Abstract: In order to further explore the preliminary findings provided by animal models and observational clinical studies that suggests there may be a beneficial effect of modest cooling for TBI, randomised trials designed to explore the effect of these interventions on patient-centred outcomes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Unfortunately, each trial failed to show benefit; several therapies were deleterious. 1017 We therefore propose in this review a new framework to guide future preclinical and clinical trials to optimize the immune response to TBI:…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…Unfortunately, each trial failed to show benefit; several therapies were deleterious. 1017 We therefore propose in this review a new framework to guide future preclinical and clinical trials to optimize the immune response to TBI:…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…Furthermore, they reported that males and females respond differently to post‐traumatic hypothermia after TBI; overall contusion volume was significantly reduced in males but not in females (Suzuki et al, ). This finding is especially important because the debate about the clinical benefits of therapeutic hypothermia continues, with recent randomized control trials in adults and children actually that suggesting hypothermia could cause more harm than benefit (Saxena et al, ; Andrews et al, ; Maekawa et al, ). However, these trials, like many others in TBI research, failed to separate and analyze sex differences, which the data from Suzuki et al () suggest could be a critical element in the role of therapeutic hypothermia in TBI.…”
Section: Therapeutic Hypothermiamentioning
confidence: 99%
“…A review by Cochrane and colleagues concluded that there is no evidence that induced hypothermia is beneficial in the treatment of traumatic head injury [ 339 ]. In addition, it suggested that there is an increase in pulmonary infections with the intervention of hypothermia compared to controls [ 340 ]. While considering the numerous variables in different clinical trials, the Brain Trauma Foundation states that six clinical tries of moderate quality did not clearly associate hypothermia with consistent and statistically significant reductions in mortality, but did find benefit in the fact that the same patients were more likely to have favorable neurological outcomes, defined as GCS scores of 4 or 5.…”
Section: Treatment Strategies and Modalities After Tbimentioning
confidence: 99%